EXAMINING THE IMPACT OF PRODUCT AND PROMOTION ON ONLINE PURCHASING DECISIONS THROUGH PURCHASE MOTIVATION - Aditya Rudy Wicaksono; Siti Asiyah; Ridwan Basalamah (Pena Cendekia Insani, 2025)
This study aims to analyze the influence of products and promotions on consumer purchasing decisions in the Shopee marketplace, with purchase motivation as a mediating variable. The approach used is a quantitative approach with an explanatory research type to test and prove the hypothesis of the relationship between variables. The theory used as a basis is the Theory of Planned Behavior (TPB), which explains that positive attitudes, social support, and perceived control play an important role in shaping consumer intentions and behavior. Data were obtained from Shopee consumers in Malang City who made non-food and non-drink purchases during the COVID-19 pandemic, using a judgmental sampling technique. The results of the study indicate that products and promotions have a positive and significant effect on purchasing decisions, both directly and through purchase motivation as a mediating variable. These findings reinforce the importance of product quality, promotional strategies, and the role of consumer motivation in increasing online purchasing decisions on e-commerce platforms.